Rest Evaluation for Active Concussion Treatment (ReAct) Protocol: a prospective cohort study of levels of physical and cognitive rest after youth sports-related concussion. Issue 4 (23rd April 2019) - Yang, Jingzhen; Yeates, Keith; Sullivan, Lindsay; Singichetti, Bhavna; Newton, Alison; Xun, Pengcheng; Taylor, H Gerry; MacDonald, James; Pommering, Thomas; Tiso, Michael; Cohen, Daniel; Huang, Yungui; et al.
Abstract : Introduction: Although current guidelines for the early clinical management of sports-related concussion (SRC) call for a gradual return-to-activity, the optimal level of rest needed to promote recovery remains unknown. This paper describes the protocol of the Rest Evaluation for Active Concussion Treatment (ReAct) study which objectively measures physical and cognitive rest following SRC and its relation to recovery among youth athletes. Methods and analysis: Youth athletes aged 11–17 years are recruited preinjury and enrolled within 72 hours following a physician-diagnosed concussion. Injury information and acute clinical presentation are assessed at the time of injury. Youth participants are prospectively followed to objectively monitor daily physical and cognitive rest using two electronic devices: ActiGraph (to measure physical rest and sleep) and Narrative Clip (to measure cognitive rest), along with self-reported postconcussive symptoms using daily surveys. Other concussion outcomes, including functional outcomes, are assessed by surveying youth and their parents at three time points: (1) within 72 hours of injury, (2) at day 7 postenrolment and (3) at symptom resolution (or a maximum of 45 days postconcussion). Ethics and dissemination: This study has received ethical approval from the Institutional Review Board (IRB) at the participating institution (IRB at Nationwide Children's Hospital, IRB16-00613). The results of the study will be presented at national and international scientific conferences and published in peer-reviewed journals.